Extended Elastic Impedance Analysis for Rock Properties Prediction from Seismic Data - Ewan, Amirul Hani (2016)
In this report, Extended Elastic Inversion (EEI) is used to identify fluid and lithology in Sepat field. Result from EEI is compared with elastic parameters generated from the well log and the highest correlation is identified. EEI correlation with the elastic parameters can be as high as 90% making it very useful method of inversion. This technique is proved to be effective way of identifying to identify fluid and lithology of the reservoir. These findings have significant implications for the commercial application of EEI in the oil and gas exploration as it appears to be superior method to conventional inversion.